Real‐world utility of HCV core antigen as an alternative to HCV RNA testing: Implications for viral load and genotype. Issue 10 (1st July 2020) - Pollock, Kevin G.; McDonald, Scott A.; Gunson, Rory; McLeod, Allan; Went, April; Goldberg, David J.; Hutchinson, Sharon J.; Barclay, Stephen T.
Abstract: Following positive serology, the gold standard confirmatory test of hepatitis C virus (HCV) infection is detection of HCV RNA by PCR. We assessed the utility of HCV core antigen testing to identify active infection among those positive for anti‐HCV antibodies, when introduced to routine testing. We identified serum samples that were tested at a single laboratory in Scotland from June 2011to December 2017. Serum samples testing positive for HCV antibodies (HCV Ab positive) followed by reflex HCV core antigen (Ag) testing during the study period were identified. Those patients for whom a PCR test was requested on the baseline sample were also identified. For this group, the sensitivity and specificity of HCV Ag as a diagnostic tool were assessed using HCV PCR as gold standard. In our cohort of 744 patients, we demonstrated a sensitivity of 82.1% (95% CI 77.1%‐86.2%) and a specificity of 99.8% (95% CI 98.6%‐100%). Genotype 3 was associated with increased odds of a false‐negative result (OR = 3.59, 95% CI: 1.32‐9.71), and reduced odds of a false negative were associated with older age (odds ratio (OR)=0.92, 95% CI: 0.88‐0.97 per year) and viral load (OR = 0.10, 95% CI: 0.05‐0.21 per log10 IU/ml). While the implementation of HCV core antigen testing for diagnosis could lead to significant cost savings in national screening programmes, our data suggest that a significant proportion of HCV‐infected individuals may be missed. These findings have implications for HCV diagnosis and determination of viral clearance after treatment, particularly in low‐ and middle‐income regions, where genotype 3 is prevalent.